Engineering Geology of Sidosari Area, Magelang, Central Java, Indonesia - I Gde Budi Indrawan; Diyaning Ratri (Journal of Applied Geology, 2017)
Development of settlement area in Sidosari area and the surroundings requires complete understanding of the engineering geological conditions, including susceptibility to landslides, to prevent damaged properties and loss of lives. Surface engineering geological mapping at a 1:25000 scale was conducted to develop a detailed landslide susceptibility map for spatial planning and to identify most controlling factor of landslides in the research area based on conditions of geomorphology, rock and soil, geological structure, groundwater seepage, and land use. The engineering geological mapping showed that landslides commonly occurred in the moderate slopes of the denudational hill landform having slope inclination ranging from 9 to 17°, in the areas covered by residual soils of the vitric tuff 2 unit, in the areas of no groundwater seepage, and in the settlement areas, including in Kranjang Lor area where soil creeping occurred. The high susceptibility zone covered 55.5 % of the research area and was characterized by having slope inclinations ranging from 9 to 35°, engineering geological units of vitric tuff 2 and tuff breccia, and land uses of rice and dry ﬁelds and settlement. The low cohesion and very high swelling potential of the residual soils of the vitric tuff 2 unit were considered to be the main controlling factor of landslides in the research area.